1997
DOI: 10.1111/j.1365-246x.1997.tb01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and scattering attenuation from observed seismic codas in the Almeria Basin (southeastern Iberian Peninsula)

Abstract: S U M M A R YThe anelastic attenuation in the Almeria Basin (southeastern Iberian Peninsula) is investigated by using seismic data collected during the summer of 1991. A multiple-lapse time-window analysis is applied to high-frequency seismograms corresponding to 20 shallow seismic events with low magnitudes ( m 12.5) and distances less than 71 km, recorded at six short-period seismographic stations. We have constructed corrected geometrical spreading and normalized energy-distance curves for the region over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 31 publications
(50 reference statements)
2
26
0
Order By: Relevance
“…This may reflect the difference in the character of the regions studied. PUJADES et al (1997) have shown that a high intrinsic attenuation quality factor can be found in the regions where low coda-Q b values are estimated. The average Q seff value for the outer Himalaya obtained from the analysis of the 1986 Dharmsala earthquake in the Himachal sector is 240 for an epicentral distance range of 6-25 km .…”
Section: Q Seff Values In Uttaranchal Sector and Himalaya Frontal Arementioning
confidence: 97%
“…This may reflect the difference in the character of the regions studied. PUJADES et al (1997) have shown that a high intrinsic attenuation quality factor can be found in the regions where low coda-Q b values are estimated. The average Q seff value for the outer Himalaya obtained from the analysis of the 1986 Dharmsala earthquake in the Himachal sector is 240 for an epicentral distance range of 6-25 km .…”
Section: Q Seff Values In Uttaranchal Sector and Himalaya Frontal Arementioning
confidence: 97%
“…The DSMC models are labeled with source depths (0, 5, 10, 15, and 20) Model Freq (Hz) (Mayeda et al, 1992), Kagoshima, Chubu, Shikoku, Japan (Hoshiba, 1993), and the Canary Island (Canas et al, 1998). Dashed lines represent South Apennines (Bianco et al, 2002), Furiuri, Italia (Bianco et al, 2005), Southern Spain (Akinci et al, 1995), and Almeria, Southeastern Spain (Pujades et al, 1997). For the previous study in Korean Peninsula is Southeastern Korea (Chung & Yoshimoto, 2013), and Korea (Chung et al, 2010) (Fig.…”
mentioning
confidence: 99%
“…Several studies showed that a correct velocity structure instead of a uniform half-space model should serve to better define the attenuation characteristics under the study area of consideration (e.g., see MAYEDA et al, 1992;HOSHIBA 1993;AKINCI et al, 1995;HOSHIBA, 1997;PUJADES et al, 1997;MARGERIN et al, 1999;AKINCI and EYIDOG AN, 2000;HOSHIBA et al, 2001;UGALDE et al, 2002;BIANCO et al, 2002 and2005). Therefore, the present results are only reasonably correct under the simplifying assumptions outlined above.…”
Section: Introductionmentioning
confidence: 38%